Precoating: uma alternativa mais econômica para melhorar a performance dos meios filtrantes em filtros de mangas da indústria siderúrgica - Melo, Bruna Râmela de (2021)
The emission of particulate matter into the atmosphere is a concern because of its environmental and human health impacts. Among the equipment used in the control of particulate material, the bag filter stands out, with a collection efficiency of up to 99.9%. There are several filter media on the market and choosing them is a challenge. Most of them, when new, have low collection efficiency, so it is necessary to carry out surface treatments to obtain a better performance. However, this surface treatment increases the pressure drop and the cost of the filter. Thus, investigating techniques with lower cost, such as precoating, presents a promising alternative to reduce the operational costs of bag filters. This technique consists of coating the fabric with a particulate material to initiate surface filtration. For its efficient use, it is necessary to know the ideal mass of precoat material and which characteristics guarantee a high filtration efficiency. Therefore, the present work evaluated the performance of different precoating powders in bag filters in the filtration of steelworks powder. For this investigation, two precoat powders (limestone and diatomaceous earth) were evaluated and different masses of materials were deposited on the filter media (PE, PE/PTFE Resin, and PE/Epitropic), which were evaluated for the collection efficiency of micro and nanoparticles, porosity of precoating and mass retained after the cleaning pulse. The results were compared with a filter coated with a PTFE membrane (PE/PTFE). The characterizations of particulate materials (particle size distribution, density, shape, and circularity) and filter media (porosity, average fiber diameter, permeability, and thickness) were carried out to understand the characteristics that impact the performance of the coating. The first filtration cycle for filter media with and without precoating was also evaluated. PEa part/PTFE showed collection efficiency above 94% for micro and nanoparticles. The other filters even showed values above 60% for microparticles collection efficiency and values above 20% for nanoparticles. By the addition of precoating, there was an increase in these values, which varied according to the coating mass deposited on the filters, with efficiencies from 80% for microparticles, to results higher than that found for PE/PTFE for both precoat powders. For nanoparticles, efficiency results were obtained with precoat from 45%, but only with diatomaceous earth, it was possible to obtain a higher value than the membrane filter. Diatomaceous earth, due to its smaller volumetric diameter compared to limestone, filled the pores of the fabric more quickly, resulting in a faster increase in pressure drop, a more compact coating, with a porosity 2x greater than that obtained for limestone and better performance in collection efficiency. About the results of retained coating mass after the cleaning pulse, values obtained for limestone were below 10% and were below 40% for diatomaceous earth. Precoating, in the first filtration cycle, did not impact the cycle time but increased the retained mass and the residual pressure drop. However, these values were lower than those obtained by PE/PTFE. In this way, precoating, for presenting a good performance in the collection efficiency in filters of lower cost, compared to PE/PTFE, is a good alternative to reduce spending on bag filters.